THE ACT OF ABDUCTION AND WOMEN TRAFFICKING IN NON-INTERNATIONAL ARMED CONFLICT (NIAC): BOKO HARAM CASE - Astrid Adelina; Nadhifa Khairunissa Ishadi (Padjadjaran Journal of International Law, 2021)
ABSTRACT Armed conflict situations will always have real negative implications, one of them is the attack against civilians. Civilians are considered as non-combatant, they do not participate in armed conflicts, thus they should not be targeted and attacked. One of the civilian groups who have special protection is women. But, in reality, women still frequently become the main victim. In the case of non-international armed conflict between Nigeria and Boko Haram, it is found that 2000 female students were abducted. They were sexually abused such as raped, sexual slavery, forced marriage, trafficked and ordered to commit suicide bombing. Nigeria is a state party to Additional Protocol II of the 1949 Geneva Convention as well as Rome Statute 1998. Nonetheless the crimes cannot be avoided and go unpunished. This paper highlights the analysis of the crime addressed to women from the perspective of international humanitarian law and international criminal law particularly in regards to the law enforcement. Research indicates that there is impunity which causes unwillingness of Nigeria to enforce the law against Boko Haram. Hence the international mechanism through ICC can be the best option to bring justice. Keywords: Boko Haram, International Criminal Law, International Humanitarian Law, Non-International Armed Conflict, Women. ABSTRAK Keadaan konflik bersenjata akan selalu memiliki implikasi negatif yang nyata, salah satunya terhadap pihak sipil. Pihak sipil disebut sebagai non-kombatan, yaitu orang-orang yang tidak berpartisipasi di dalam konflik bersenjata, yang berarti orang-orang tersebut bukanlah target dan tidak boleh diserang. Salah satu pihak yang mendapat perlindungan khusus adalah perempuan. Tetapi, pada kenyataannya perempuan masih sering menjadi korban utama. dalam konflik non-internasional antara Nigeria dan Boko Haram, ditemukan fakta 2000 pelajar perempuan diculik. Mereka mengalami berbagai kekerasan seksual seperti pemerkosaan, budak seks, kawin paksa, perdagangan manusia, dan bahkan untuk melakukan bom bunuh diri. Nigeria adalah negara pihak Protokol Tambahan II Konvensi Jenewa 1949 dan Statuta Roma 1998. Namun kejahatan-kejahatan tersebut tidak dapat terhindari dan tidak diadili. Tulisan ini menitikberatkan penegakan hukum terkait kejahatan terhadap perempuan dilihat dari perspektif hukum humaniter internasional dan hukum pidana internasional. Berdasarkan penelitian, terdapat praktek impunitas yang menunjukan ketidakmauan Nigeria untuk melakukan penegakan hukum terhadap Boko Haram sebagai pelaku kejahatan tersebut. Oleh karenanya mekanisme ICC dapat merupakan pilihan terbaik untuk menegakan keadilan. Kata Kunci: Boko Haram, Hukum Humaniter Internasional, Hukum Pidana Internasional, Konflik Bersenjata Non-Internasional, Perempuan